Period of Homogeneous Oscillations in the B-Z System Involving a Tetraazamacrocyclic Complex - Hu, Gang; Hu, Lin; Xu, Zhi-Qiang; Xie, Fu-Xing; Ni, Shi-Sheng (Asian Journal of Chemistry, 2016)
This work is primarily an experimental investigation of a tetraazamacrocyclic nickel complex catalyzed system. The complex contains unsaturated macrocyclic ligand 11,13-dimethyl-1,4,7,10-tetetraazacyclotrideca-1,10,12-triene. We measure the reactions by monitoring the changes of the potentials of platinum and bromide selective electrode. The emphasis is placed on the properties of the period of homogeneous oscillations. It is found that the mean period depends on the initial concentrations of reactants: T(s) = 0.43[BrO3–]00.75, [H2SO4]0-4.45, [CH3COCOOH]0-2.42 (mol dm-3)6.12. The period is not perfectly constant. The effects of concentrations of the components on the waveforms are also discussed.